2020
DOI: 10.4103/jispcd.jispcd_342_19
|View full text |Cite
|
Sign up to set email alerts
|

Third molar angulation changes in Class II div I malocclusion subjects treated with extraction of four premolars: A retrospective study

Abstract: A BSTRACT Aim: The aim of this study was to assess the changes in maxillary and mandibular third molar inclinations in individuals with class II div 1 malocclusion, before and after orthodontic treatment with extraction of all four first premolars. Materials and Methods: This retrospective study consisted of the pretreatment and posttreatment records of 30 patients that were obtained from the archives of the department of orthodontics and dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In as much, a variety of reference points has been used by various researchers to estimate the angulation of the third molar. Thus, the mandibular plane has been utilized as a reference plane in other studies [4,31,43] of which only Shashidhar et al [31] found a statistically significant difference in the alteration of the angulation of the lower third molar by examining only cephalometric x-rays, whereas the other two studies examined both cephalometric and panoramic x-rays. Moreover, the Frankfurt plane was used as the reference plane by two studies [14,39], which both examined panoramic x-rays and found no difference in the angulation of the lower third molar before and after the orthodontic treatment between an extraction and non-extraction group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In as much, a variety of reference points has been used by various researchers to estimate the angulation of the third molar. Thus, the mandibular plane has been utilized as a reference plane in other studies [4,31,43] of which only Shashidhar et al [31] found a statistically significant difference in the alteration of the angulation of the lower third molar by examining only cephalometric x-rays, whereas the other two studies examined both cephalometric and panoramic x-rays. Moreover, the Frankfurt plane was used as the reference plane by two studies [14,39], which both examined panoramic x-rays and found no difference in the angulation of the lower third molar before and after the orthodontic treatment between an extraction and non-extraction group.…”
mentioning
confidence: 99%
“…In our study, we evaluated the angle formed between the long axis of the third lower molar and the long axis of the second lower molar. According to Shashidhar et al [31], this is not a stable measurement as the second molars can be tipped in a mesial/distal/lingual/buccal direction prior to the start of the treatment and then get corrected during orthodontic treatment. To avoid the implication of the second molar's spatial orientation in investigating the third molar angulation, the lower third molar angulation was evaluated only in the posttreatment OPG.…”
mentioning
confidence: 99%